آفاق التطور والازدهار لمراكز تحفيظ القرآن الكريم في نيجيريا: مشكلات وحلول - Garba, Ahmad (Al-Muyassar: Journal of Arabic Education, 2025)
فاق التطور والازدهار لمراكز تحفيظ القرآن الكريم في نيجيريا: مشكلات وحلولPROSPECTS FOR GROWTH AND DEVELOPMENT OF QURAN MEMORIZATION CENTERS IN NIGERIA: PROBLEMS AND SOLUTIONSAhmad GarbaPhone +234 07030215179ORCID:0000-0001-8757-8056Federal University of Kashere, Gombe State NigeriaDepartment of Arts and Social Science EducationAhmadgarba315@gmail.comمستخلص البحثلا شك أن أهمية التعليم لا يمكن لأي دولة أن تتجاهلها، وفي عالم اليوم أصبح التعليم ضرورة مطلقة لتحقيق التنمية الاقتصادية والاجتماعية لأي دولة، ولا يخفى على أحد أهمية التعليم والتعلم في عصرنا هذا، وخاصة بالنسبة للدول النامية، حيث يعتبر الجهل والتنمية والهوية هي ثلاثية المشكلة لتلك الدول. لذلك فإن التعليم يمثل محوراً أساسياً لتقدمها. ظهرت مراكز تحفيظ القرآن الكريم في نيجيريا نتيجة لجهود العلماء لتحديث المدارس الإسلامية، ورأى العلماء المسلمون ضرورة إدخال بعض النظم والتعديلات على المناهج المدرسية إلى جانب المحتوى العلمي للمدارس الدينية التقليدية. وتمتعت هذه المراكز بقدر من الاستقلال عن الدولة وتنظيمها وتدخلاتها، حيث تركز في المقام الأول على حفظ القرآن الكريم. ويتم التدريس في هذه المراكز من قبل المعلمين العائدين من مصر أو دول الخليج الذين حصلوا على درجة من التعليم الحديث أو بعض التدريب الرسمي للمعلمين. وكانت هذه المراكز تحتوي على مناهج وكتب مقررة تتعلق بالقرآن الكريم وعلومه. وتختلف اللغة الرسمية في هذه المراكز بحسب موقعها، ولكنها إما أن تكون اللغة العربية أو اللغة المحلية لموقع تلك المراكز، وكانت تحقق طموحات الآباء في أن يجمع أبناؤهم بين دراسة العلوم الإسلامية وحفظ القرآن الكريم، ولكن للأسف لا تزال هذه المراكز تعاني من بعض المشاكل التي تعيق تطورها الملحوظ، كما تختلف هذه المراكز عن بعضها البعض من حيث المناهج، ونوعية التعليم، والعملية التعليمية. وعلى هذا الأساس، تهدف هذه الورقة إلى تسليط الضوء على دور مراكز تحفيظ القرآن الكريم في نيجيريا، والتوصل إلى بعض الحلول الممكنة للمشاكل التي تعاني منها. وقد استخدم الباحث المنهج الوصفي؛ من خلال تتبع المواد العلمية حول تاريخ ازدهار هذه المراكز في نيجيريا، ومدى تأثيرها على مسلمين نيجيريا. وكانت نتيجة هذه الدراسة أن مراكز تحفيظ القرآن الكريم ساهمت بشكل كبير في تعزيز وعي الشباب المسلم النيجيري في الحفظ وتعلم العلوم الدينية. الكلمات المفتاحية: مركز، خلاوى، منهج، مشكلة، نيجيريا.ABSTRACT No doubt the importance of education cannot be ignored by any country, and in today’s world education has become an utmost necessity for achieving the economic and social development of any country. In our time, the importance of education and learning is obvious and clear to everyone, especially for developing countries, where ignorance, development and identity are considered as part of their problems. For those countries, this is why education represents a fundamental axis for their advancement. Centers for Quranic memorization appeared in Nigeria as a result of the efforts of scholars to modernize Islamic schools. Muslim scholars saw the need to introduce some policies and modifications in the school curriculum along with the scientific content of traditional religious schools. This has given the centers a certain degree of independence as it mainly focuses on Quranic memorization. These centers are taught by teachers returning from Egypt or the Gulf countries who have had some modern education or some formal training for teachers. These centers have curricula and prescribed books related to Holy Qur’an and its sciences. The official language in these centers varies depending on their location, but it is either Arabic or the local language of the location of those centers, and it fulfills the ambition of parents for their children to combine the study of Islamic sciences and memorization of the Holy Qur’an. However, it is very regrettable that these centers are still facing some challenges and problems that hinder it from a brilliant and tangible development. These centers also differ from each other in terms of curricula, quality of education, and educational processes. It is On this basis, this paper aims to highlights on the role of modern Quranic memorization centers in Nigeria, and to come up with some possible solutions to the problems it encounters. The researcher used a descriptive research design. This was done by tracking scientific materials on the history and emergence of these centers in Nigeria, and the extent of it impact on Nigerian Muslims, the result of this study concluded that the centers for memorizing the Holy Qur’an contributed greatly to enhancing the conscious of Nigerian Muslim youth towards memorization of the holy Quran and learning Islamic sciences.Keywords: center, tsangaya, approach, problem, Nigeria.